Matrices related to orthogonal hypercomplex polynomial systems - Cação, I. (2018)
We show how special well known matrices, namely, the creation and shift matrices play an important role on a matrix representation of orthogonal systems of polynomials with a hypercomplex variable and values in a Cli ord algebra.